Ethical and definitional considerations in research on child sexual violence in India - Radhika Dayal; Ameeta S. Kalokhe; Vikas Choudhry; Divya Pillai; Klaus Beier; Vikram Patel (BMC, 2018)
Abstract Background While critically important, child sexual violence (CSV) research poses numerous ethical and safety challenges. Recently, the studies dedicated to understanding and addressing CSV in India have been on the rise, but no published ethical guidelines to direct such research currently exist. To help inform ethical and safety recommendations for the design, conduct, and reporting of future CSV research in India and similar settings, we systematically reviewed the ethics and safety practices reported in recent Indian CSV literature. Methods A multi-tiered approach was used to understand current ethical practices and gaps: 1) systematic review of Indian CSV studies published over the past decade, 2) examination of existing guidelines on related topics to develop an ethical framework, 3) development of an ethics checklist based on the recommendations from the surveyed guidelines, and 4) application of the checklist to each of the reviewed studies. Result Our search yielded 51 eligible studies. From each, data from 6 major thematic areas was extracted: informed consent, confidentiality, selection, training, and protection of study team members, validity of CSV measurement methods, measures to minimize participant harm, and participant compensation. Several gaps were noted: only two-thirds reported approval by ethics committees, obtaining informed consent, and assured participants of confidentiality. Only 25% (13/51) reported assessing ongoing CSV risk and providing necessary support services, none noted whether ongoing CSV was reported to authorities (required by Indian law), and none reported safeguards to protect staff from the effects of conducting CSV research. Further, 43% (22/51) limited surveillance of CSV to one form of abuse and/or used a "loaded term," increasing the potential for underreporting. Conclusions Through enhancing understanding of current ethical practices and gaps in CSV research in India, this systematic review informs reporting protocols and future guidelines for CSV research in India and other similar settings.